Primitive Thinking Figuring Alterity in German Modernity - Gess, Nicola (PARADIGMS, 2022)
This book examines the discourse on 'primitive thinking' in early 20th century Germany. It explores texts from the social sciences, writings on art and language and - most　centrally - literary works by Robert Musil, Walter Benjamin, Gottfried Benn and Robert Müller, focusing on three figures of alterity prominent in European primitivism:　indigenous cultures, children, and the mentally ill.